2021
DOI: 10.1186/s12935-021-02298-9
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and dopamine receptor D1 as a novel favourable biomarker for hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) remains one of the most common malignant tumours worldwide. Therefore, the identification and development of sensitivity- genes as novel diagnostic markers and effective therapeutic targets is urgently needed. Dopamine and dopamine receptor D1 (DRD1) are reported to be involved in the progression of various cancers. However, the crucial role of DRD1 in HCC malignant activities remains unclear. Methods We en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…DRD1 is highly expressed in hepatocellular carcinoma tissue, and high expression of DRD1 is associated with poor prognosis in liver cancer patients. 82 The DA level in the serum of HCC patients is lower than that in the serum of normal healthy individuals. However, treating HCC cells with DA can increase cell their proliferation, indicating that DA is an important factor in tumour growth.…”
Section: Roles Of Dopamine and Dopamine Receptors In Liver Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…DRD1 is highly expressed in hepatocellular carcinoma tissue, and high expression of DRD1 is associated with poor prognosis in liver cancer patients. 82 The DA level in the serum of HCC patients is lower than that in the serum of normal healthy individuals. However, treating HCC cells with DA can increase cell their proliferation, indicating that DA is an important factor in tumour growth.…”
Section: Roles Of Dopamine and Dopamine Receptors In Liver Diseasementioning
confidence: 94%
“…DA promotes the proliferation and metastasis of HCC cells. DRD1 is highly expressed in hepatocellular carcinoma tissue, and high expression of DRD1 is associated with poor prognosis in liver cancer patients 82 . The DA level in the serum of HCC patients is lower than that in the serum of normal healthy individuals.…”
Section: Roles Of Dopamine and Dopamine Receptors In Liver Diseasementioning
confidence: 97%
“…In contrast, the roles of D1Rs in carcinogenesis are not as well described, but D1Rs have recently been identified as novel tumor suppressors in multiple cancers including breast cancer, glioblastoma, prolactinoma, endometrial cancer, and possibly gastrointestinal cancers, osteosarcoma, and liver cancers [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. For example, in breast cancer, DRD1 agonists have been shown to inhibit breast cancer cell growth in vitro [ 23 , 24 ], reduce cancer stemness and cell mobility in vitro [ 25 ], and reduce tumor growth [ 23 ] and lung metastasis [ 25 ] in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In glioblastoma (GBM), DRD1 expression is associated with a more favorable prognosis [ 27 ], and one study found that DRD1 agonism inhibited cell growth through disrupting autophagic flux and showed that the DRD1 agonist SKF83959 and the chemotherapeutic temozolomide have a synergistic antitumor effect [ 27 ]. These studies point to a tumor suppressive role for D1Rs, but in other tumor types, the role of D1Rs is less clear as, for example, in both HCC and biliary tumors there are conflicting reports of DRD1's role [ 32 , 33 , 34 , 35 ]. In summary, there is growing evidence for a tumor suppressive role for D1Rs in multiple tumor types, but more work is required to elucidate which tumor types and patient groups could benefit from therapeutic targeting of D1Rs.…”
Section: Introductionmentioning
confidence: 99%
“…There are five receptors DRD1, DRD2, DRD3, DRD4, and DRD5, which are divided into two subgroups: D1-like receptors (DRD1 and DRD5) and D2-like receptors (DRD2, DRD3, and DRD4) [ 8 ]. Among them, DRD1 and DRD2 subtypes are among the most studied in terms of their role in cancer growth and progression [ 9 ]. Several papers revealed increased mRNA and protein levels of DRD2 in pancreatic, colon, prostate, and breast cancers [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%